USING PHOTOGRAPHY FOR SOCIAL CONTROL AND POLITICAL MANIPULATION - Svetlana A. Afanasyeva (Вестник Донского государственного технического университета, 2018)
The role of photography in the process of the social control of the power over the actions, people’s behaviour, and forming public opinion is considered. Photography is presented as a manipulative technology of the information war.